A NEW DIRECTION IN SCHOLARSHIP IN POSTCOLONIAL PSYCHOLOGY - Swartz, Leslie (PINS-Psychology in Society, 2025)
Hook, Derek (2012) A critical psychology of the postcolonial: The mind of apartheid. London & New York: Routledge. ISBN 978-0-415-58757-0 pbk. Pages x + 251. This is an important book for a number of reasons. Derek Hook fearlessly takes on the complicated question of what apartheid meant and means, going far beyond the tradition of uni-dimensional psychological explanations. In helping us understand apartheid racism (and its various aftermaths) he achieves something remarkable – he takes the psychological seriously, does not trivialise it, and at the same time infuses the psychological with a very broad postcolonial understanding.